2015
DOI: 10.1016/j.vaccine.2015.01.043
|View full text |Cite
|
Sign up to set email alerts
|

Serogroup A meningococcal conjugate (PsA-TT) vaccine coverage and measles vaccine coverage in Burkina Faso—Implications for introduction of PsA-TT into the Expanded Programme on Immunization

Abstract: Background A new serogroup A meningococcal conjugate vaccine (PsA-TT, MenAfriVac™) has been developed to combat devastating serogroup A Neisseria meningitis (MenA) epidemics in Africa. A mass immunization campaign targeting 1–29 year olds was conducted in Burkina Faso in December 2010. Protection of subsequent infant cohorts will be necessary through either introduction of PsA-TT into the routine Expanded Programme on Immunization (EPI) or periodic repeat mass vaccination campaigns. Objectives To inform futu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…Figure 3, Figure 5 and Figure S9 show that trajectories generated by our model also match other key properties of meningococcal epidemics in Niger (e.g., age-distribution of cases, age-specific carriage prevalence, average weekly meningococcal incidence at national and district level, and number of districts in each year between 2002-2015 where the threshold of 10 meningitis cases per 100,000 population is exceeded). Table 3 Table 3 Age 5+ years [3][4][5] years [29,57] PMC [10][11][12][13][14][15][16][17][18][19][20] years [39,55] Delay between administration of vaccine and the establishment of immunity PMP or PMC 2 weeks [58] Vaccine uptake Routine # 80%-90% [59] Reactive and Preventive (within 10 days) 90%-100% [60][61][62] PMC: Polyvalent meningococcal conjugate; PMP: Polyvalent meningococcal polysaccharide. * These parameters are sampled for each individual in a simulated trajectory.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 3, Figure 5 and Figure S9 show that trajectories generated by our model also match other key properties of meningococcal epidemics in Niger (e.g., age-distribution of cases, age-specific carriage prevalence, average weekly meningococcal incidence at national and district level, and number of districts in each year between 2002-2015 where the threshold of 10 meningitis cases per 100,000 population is exceeded). Table 3 Table 3 Age 5+ years [3][4][5] years [29,57] PMC [10][11][12][13][14][15][16][17][18][19][20] years [39,55] Delay between administration of vaccine and the establishment of immunity PMP or PMC 2 weeks [58] Vaccine uptake Routine # 80%-90% [59] Reactive and Preventive (within 10 days) 90%-100% [60][61][62] PMC: Polyvalent meningococcal conjugate; PMP: Polyvalent meningococcal polysaccharide. * These parameters are sampled for each individual in a simulated trajectory.…”
Section: Discussionmentioning
confidence: 99%
“… Source: World Health Organization Inter-country Support Team report on PsA-TT campaigns (meningvax.org). a Regional and weighted national PsA-TT vaccine coverage (95% confidence interval) [ 9 ]. …”
Section: Vaccine Rolloutmentioning
confidence: 99%
“…Administrative coverage may be reported as >100% because of inaccurate population size estimates and because some people >29 years might have received the vaccine [64]. Excellent vaccination coverage was generally obtained, but studies also showed that there were local variations between districts and also between villages in the same district [68,69].…”
Section: Vaccination Coveragementioning
confidence: 99%
“…Vaccine uptake was lower in the age group 15-29 years, but did not differ by gender. Another study from Burkina Faso showed that the primary predictor for MenAfriVac vaccination among all age groups was that the head of the household was informed of the campaign [69]. MVP reported highest vaccination coverage rates in the 1-4 age group and lowest rates in the 15-29 and the 5-14 age groups in Cameroon and Chad, respectively [58].…”
Section: Vaccination Coveragementioning
confidence: 99%
See 1 more Smart Citation